A new species of the genus Pleonexes Spence Bate, 1857 (Senticaudata, Ampithoidae) from Gujarat State, India - Thacker, Dimple; Myers, Alan A.; Trivedi, Jigneshkumar N. (Zootaxa, 2026)
In the present study, a new species, Pleonexes spencebatei sp. nov., is described on the basis of specimens collected from Gujarat State, India. This new species is morphologically similar to P. nargessi Momtazi & Maghsoudlou, 2020, but can be differentiated by having, peduncle article 1 of antenna 1 without a distal robust seta, maxilla 1 inner plate with only 1 seta, more slender gnathopods, and telson lacking tubercles.